Well-being inequities in eleven rural Georgia communities: A latent profile analysis - April K. Hermstad; Regine Haardörfer; Kimberly Jacob Arriola; Peter Stoepker; Emily L. Leung; Michelle C. Kegler (PLoS ONE, 2025)
Personal well-being is a broad term that encompasses life domains that are not strictly health related, including social, emotional, financial, and environmental factors. Well-being is highly correlated with a range of sociodemographics and health outcomes. Little is known about well-being in rural communities, although the literature suggests that rural communities may be structurally and demographically disadvantaged regarding well-being. This cross-sectional study examined sociodemographic and health-related differences in key well-being domains, using the Personal Well-being Index (PWI). Latent Profile Analysis was used to identify demographic traits and health-related factors associated with differing levels of well-being. As part of a cross-site evaluation of a rural health initiative, we conducted a random, population-based mail survey in 11 rural counties in Georgia (USA). Between December 2018 and June 2019, surveys were mailed to 10,621 households, with 2,788 individuals completing the survey (26.2% response rate). We observed consistent differences in PWI scores and for each domain comprising the PWI across all sociodemographic categories, with characteristics that have historically conferred advantages in the USA (e.g., male gender, White race) generally being associated with greater well-being. The Latent Profile Analysis revealed five distinct well-being profiles reflecting different levels of well-being, with most respondents falling into the Very High or High well-being profile groups. Despite structural and demographic disadvantages, well-being and its sociodemographic and health-related correlates in this rural sample were comparable to that of urban settings. Coalitions working in partnership with researchers and evaluators may be an effective mechanism for identifying the factors that influence well-being and health. Interventions on social determinants of health may help determine what approaches are successful and best promote well-being, in addition to health, while also reducing socioeconomic inequities.